Targeted next-generation sequencing identifies a novel nonsense mutation in SPTB for hereditary spherocytosis: A case report of a Korean family. Issue 3 (January 2018) - Shin, Soyoung; Jang, Woori; Kim, Myungshin; Kim, Yonggoo; Park, Suk Young; Park, Joonhong; Yang, Young Jun
Abstract: Rationale: Hereditary spherocytosis (HS) is an inherited disorder characterized by the presence of spherical-shaped red blood cells (RBCs) on the peripheral blood (PB) smear. To date, a number of mutations in 5 genes have been identified and the mutations in SPTB gene account for about 20% patients. Patient concerns: A 65-year-old female had been diagnosed as hemolytic anemia 30 years ago, based on a history of persistent anemia and hyperbilirubinemia for several years. She received RBC transfusion several times and a cholecystectomy roughly 20 years ago before. Round, densely staining spherical-shaped erythrocytes (spherocytes) were frequently found on the PB smear. Numerous spherocytes were frequently found in the PB smears of symptomatic family members, her 3rd son and his 2 grandchildren. Diagnosis: One heterozygous mutation of SPTB was identified by targeted next-generation sequencing (NGS). The nonsense mutation, c.1956G>A (p.Trp652*), in exon 13 was confirmed by Sanger sequencing and thus the proband was diagnosed with HS. Interventions: The proband underwent a splenectomy due to transfusion-refractory anemia and splenomegaly. Outcomes: After the splenectomy, her hemoglobin level improved to normal range (14.1 g/dL) and her bilirubin levels decreased dramatically (total bilirubin 1.9 mg/dL; direct bilirubin 0.6 mg/dL). Lessons: We suggest that NGS of causative genes could be a useful diagnostic tool for the genetically heterogeneous RBC membrane disorders, especially in cases with a mild or atypical clinical manifestation.